(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article covers the development of teaching methodology for general secondary school teachers based on virtual technologies. The influence of virtual technologies on the educational process, the need to improve the digital competence of teachers, and the introduction of modern teaching methods are analyzed. Ways to increase the effectiveness of using virtual platforms and electronic resources in pedagogical activity will also be considered. The article presents scientific reflections on the advantages, challenges, and development prospects of the teaching methodology based on virtual technologies. Based on the research results, recommendations are given for teachers to master modern educational technologies.